2011
DOI: 10.1007/s12195-011-0172-0
|View full text |Cite
|
Sign up to set email alerts
|

Fragmin/Protamine Microparticles (F/P MPs) as Cell Carriers Enhance the Formation and Growth of Tumors In Vivo

Abstract: Mixing a low-molecular-weight heparin (e.g., fragmin) with protamine results in the formation of waterinsoluble fragmin/protamine microparticles (F/P MPs) approximately 0.5-3 lm in diameter. In this study, we investigated the ability of F/P MPs to improve the viability of Lewis lung (3LL) cancer cells, B16 (B16) melanoma cells, and a human hepatoma (Huh7) cell line in a suspension culture, and the ability of F/P MPs to enhance tumor take rate and growth in vivo. F/P MPs rapidly bound to the surface of the cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…LMW-H/P MPs also bind to the surface of various adhesive tumor cells, promoting cell-to-cell interaction and increase cellular aggregation with the LMW-H/P MPs. The tumor cells/LMW-H/P MPs-aggregates substantially promote cell survival and proliferation of those tumor cells in vitro , and reliably induce tumor formation and rapid tumor growth in vivo [ 26 ]. Taken together, LMW-H/P MPs constitute a new convenient and effective biomaterial that function as a tumor cell carrier in vivo .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…LMW-H/P MPs also bind to the surface of various adhesive tumor cells, promoting cell-to-cell interaction and increase cellular aggregation with the LMW-H/P MPs. The tumor cells/LMW-H/P MPs-aggregates substantially promote cell survival and proliferation of those tumor cells in vitro , and reliably induce tumor formation and rapid tumor growth in vivo [ 26 ]. Taken together, LMW-H/P MPs constitute a new convenient and effective biomaterial that function as a tumor cell carrier in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…The LMW-H/P MPs generate a stable paste-like coating through complete drying. It is probable that polypeptides, such as FGF-2, interleukin (IL)-3 and granulocyte/macrophage-colony stimulating factor (GM-CSF), once bound to the LMW-H/P MPs-coated plates, are gradually released from the coated surface in vitro with a half-life of 4–6 days [ 26 ]. Furthermore, LMW-H/P MPs-coating could optimally stimulate growth of hMVECs and hDFCs in low FBS (1%)-DMEM with FGF-2 and growth of hematopoietic cell line (TF-1) with IL-3 and GM-CSF ( Figure 7 ) [ 26 ].…”
Section: A Cell Culture System Using Lmw-h/p Mps-coated Platesmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to prevent bacterial or fungal contamination, the medium was replaced with fresh medium 24 h after cell preparation. After 3 more days of culture, both attached and floating spheroids were collected, mixed with extracellular scaffold [14] and injected into nude mice subcutaneously. We did not adjust the cell number precisely at the first transplantation, since the ratio between attached and spheroid cells varied individually.…”
Section: Methodsmentioning
confidence: 99%
“…Those results indicated that LMWH/P N/MPs constitute an effective biomaterial that functions as a tumor cell carrier in vivo . The application of LMWH/P N/MPs as a tumor cell carrier offers a more reliable model in both allograft and xenograft transplantation for cancer research [ 45 , 46 ].…”
Section: Biomedical Applications Of Low Molecular Weight Heparin/pmentioning
confidence: 99%